2015
DOI: 10.1093/nar/gkv1358
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution ofcis-regulatory elements to higher order chromatin structure and expression of theCFTRlocus

Abstract: Higher order chromatin structure establishes domains that organize the genome and coordinate gene expression. However, the molecular mechanisms controlling transcription of individual loci within a topological domain (TAD) are not fully understood. The cystic fibrosis transmembrane conductance regulator (CFTR) gene provides a paradigm for investigating these mechanisms. CFTR occupies a TAD bordered by CTCF/cohesin binding sites within which are cell-type-selective cis-regulatory elements for the locus. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(110 citation statements)
references
References 63 publications
8
101
1
Order By: Relevance
“…Sub-TADs, typically contained within TADs, appear to regulate transcription by bringing a distant enhancer near the respective promoter (8,16,18,25). However, although CTCF plays a central role in establishing chromatin structure, epigenetic borders, and transcriptional activity, removal of CTCF does not invariably lead to changes in chromatin looping (26) and epigenetic marks flanking the border (12). Further, gene expression can be changed in cis at some distance from the abrogated CTCF-BS (12,27).…”
Section: Discussionmentioning
confidence: 99%
“…Sub-TADs, typically contained within TADs, appear to regulate transcription by bringing a distant enhancer near the respective promoter (8,16,18,25). However, although CTCF plays a central role in establishing chromatin structure, epigenetic borders, and transcriptional activity, removal of CTCF does not invariably lead to changes in chromatin looping (26) and epigenetic marks flanking the border (12). Further, gene expression can be changed in cis at some distance from the abrogated CTCF-BS (12,27).…”
Section: Discussionmentioning
confidence: 99%
“…Third, more recently analysis of enhancer-promoter interactions around the CFTR locus showed that the CFTR promoter engages with distinct cell-type specific distal enhancers and CTCF-bound loci in different tissues. Intriguingly, all these are contained within one tissue-invariant TAD (Smith et al, 2016; Yang et al, 2015). ChIA-PET analyses of CTCF-anchored loops between TAD boundaries and RNA polymerase-anchored chromatin loops also showed that gene regulatory interactions between gene promoters and their distal regulatory elements occur mostly within TADs (Tang et al 2015).…”
Section: The 3d Genome As Censormentioning
confidence: 99%
“…Similarly, deletion of a CTCF motif in the homologous region in a human embryonal carcinoma cell line also resulted in alterations of chromatin organization and dramatic changes in expression of genes in the locus (Xu et al, 2014). Third, deletion of CTCF binding sites at the borders of a CFTR-containing TAD in a human epithelial colorectal adenocarcinoma cell line (Caco2) altered chromatin organization and enhanced chromatin interaction between the CFTR promoter and sequences outside of the TAD (Yang et al, 2015). Fourth, comparative analysis of chromatin organization in several mammalian species revealed evolutionarily conserved TAD boundaries that are associated with conserved CTCF binding sites across species, as well as a strong correlation between the turn over of CTCF binding sites and loss or gain of TAD boundaries in these species (Vietri Rudan et al, 2015).…”
Section: Mechanisms Of Tad Formationmentioning
confidence: 99%